First Records of Male and Swollen Females of Two Species of Achlysiella (Nematoda: Pratylenchidae) - Abdul Gafur; Mike Hodda (Bogor Agricultural University, Indonesia, 2023)
Males and swollen mature females of Achlysiella trilineata and Achlysiella magniglans were discovered for the first time in Australia. These life stages confirmed that both species show well-marked sexual dimorphism in the anterior region of the body, with the males having reduced cephalic frameworks, stylets, and oesophagi. Males of A. magniglans displayed an extreme reduction in the style such that only the cone could be seen, and the rest of the esophagus was barely visible. In both species, the swollen females had postmedian vulvae, and the anterior branch of the ovary was longer than the posterior branch. In A. magniglans, the disparity in length was more pronounced, and the vulva was more posterior. The finding of swollen females confirmed the classification of both species in Achlysiella rather than Radopholus. Vermiform females of both species have large dorsal oesophageal glands and short ovaries. Justifiably, other species of Radopholus with these latter features (R. brevicaudatus, R. capitatus, and R. vacuus) should also be moved to Achlysiella.